Spatio-temporal analysis of urban dynamics in Kashmir valley (1901-2011) using geographical information system - Malik, Mohammad Imran (International Multidisciplinary Research Journal, 2012)
Kashmir valley is the most urbanized region of Indian Himalayan region. The study of distribution, growth and extent of its urban centers is vital to create a sound economic base as urban centers are reflectors of overall development of a region. The present study has been carried out using geographical information system to analyze the spatial distribution of different size class towns in different physiographic divisions of the valley. The study reveals that Srinagar is a primate city while almost all the urban centers fall in its zone of influence. The urban development in the valley is very lopsided and imbalanced with Srinagar witnessing tremendous growth and small urban centers have either recorded sluggish growth or have shown signs of stagnation. This twin process has made urban growth very complex phenomenon and a challenging task for city planners to ensure a reasonable quality of life and environment to the inhabitants. The unplanned and unregulated urbanization is leading to several kinds of environmental change which are more intensive and hazardous in the ecologically fragile Kashmir Himalayas. The present study will help in devising a balanced urban growth strategy in the region, by reducing the disparities in the levels of socio-economic development.